LEGAL PATHWAYS AND OBSTACLES IN SEEKING COMPENSATION FOR MEDICAL MALPRACTICE: A LITERATURE REVIEW OF THE STAGES OF DISPUTE RESOLUTION IN INDONESIAN CIVIL LAW - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study discusses the legal channels and obstacles in claiming compensation for medical malpractice in Indonesia through a literature review of the stages of dispute resolution in civil law. The focus of the study is on legal mechanisms, including mediation, filing lawsuits, trials, and the execution of compensation decisions, as well as the various obstacles faced by victims in the process of enforcing their rights. Using a literature review method, this study analyses legal literature, court decisions, regulations, and related documents to provide a comprehensive overview of the procedures and obstacles that arise, whether procedural, substantive, systemic, or cultural. The results of the study show that although formal legal channels are available, complex obstacles often hinder victims of malpractice from accessing justice. Therefore, improvements to the legal system, increased understanding of patient rights, and the development of alternative dispute resolution mechanisms are needed to create effective and fair legal protection.